STRATEGI KOMUNIKASI HUMAS POLDA POLDA D. I. YOGYAKARTA MELALUI SKILL DIGITAL SAVVY DI ERA DISRUPTIF - Rahmat Hidayat Asri (Expose: Jurnal Ilmu Komunikasi, 2018)
Abstract. The objectives of this research are: (1) to know the communication strategy of the Yogyakarta Police Public Relations through digital savvy skill in the disruptive era, (2) to know digital channel used in the communication strategy of the Yogyakarta Police Public Relations through digital savvy skill in the disruptive era, (3) to identify the advantages and disadvantages of the communication strategy of the Yogyakarta Police Public Relations through digital savvy skill in the disruptive era. This research is a descriptive research with qualitative technique approach. Informant as the source of data in this research is The Head of Monitoring Affairs. The methods of data collection using interview, observation, and documentation. The technique of data validity is determined using triangulations technique. Technical analysis of data using interactive models by Miles and Huberman. The result of this research shows that the communication strategy of the Yogyakarta Police Public Relations through digital savvy skill in the disruptive era are: management of internal communication through WhatsApp so that communication pattern more effective and efficient, digital media management training with material focused on digital savvy skill, management of digital channels that are active as channels of communication to the public, the community can communicate directly through social media, staff have more specific capabilities. Digital channels used are facebook, twitter, instagram, youtube channel. The advantages of the communication channel the Yogyakarta Police Public Relations become more effective and efficient. Presentation of information through digital channels more organized, interesting, easy to connect and obtain information, as well as existing staff in accordance with their fields. The drawback is the lack of staff and no multimedia sub-sector that has a focus on digital savvy.Keywords: communication strategy, public relations, digital savvy, disruptive era.